Performance Assessment of Kawasoti Water Supply and Sanitation Project, Nawalparasi, Nepal - Regmi, Pradeep; Jnawali, Shankar Mani (Journal of Lumbini Engineering College, 2023)
The Government of Nepal aimed to provide adequate basic supply of safe drinking water to all its citizens by 2023 (15thAdhar Patra, National Planning Commission). Although the national level of water supply and sanitation facility coverage is 88 and 98 percent respectively, only 25.4% of water supply projects are fully functional. The performance assessment of completed piped water supply scheme should to be assessed for the functionality and sustainability of the project. With an example of Kawasoti Small Town Water Supply Project (KSTWSP), performance of the service provider is assessed in terms of physical state, functionality, customer satisfaction, water resource management, financial management and human resource management. The major findings were that bacterial removal efficiency of slow sand filter is greater than 95 % and the turbidity from the outlet of slow sand filter was found to be less than 0.1 NTU. The study of financial data of Kawasoti WUSC shows that operating revenue is sufficient to cover the operating expenses of WUSC. The water demand for the year 2075 to 2086 were found to be (7.32, 7.58, 7.84, 8.12, 8.40, 8.69, 8.99, 9.31, 9.68, 10.07, 10.47, 10.89, 11.33 and 11.79) MLD respectively. The water production was taken as an average of 9.94 MLD. The analysis shows up to the year 2083, the system will be able to meet the water demand. So after 2083, the WUSC might need to make necessary arrangement for additional water sources to meet the water demand. Staff productivity index has been 3.70 from the year 2070 to 2075, which indicates efficient utilization of the staff. Thus the study concluded that the performance of Kawasoti WUSC is up to satisfactory level till this study year 2075.